2009
DOI: 10.1111/j.1750-3841.2008.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on the Depuration of Vibrio parahaemolyticus and Vibrio vulnificus from the American Oyster (Crassostrea virginica)

Abstract: This study investigated temperature effects on depuration for reducing Vibrio parahaemolyticus and Vibrio vulnificus in American oyster (Crassostrea virginica). Raw oysters were inoculated with 5-strain cocktail of V. parahaemolyticus or V. vulnificus to levels of 10(4) to 10(5) MPN (most probable number)/g and depurated in artificial seawater (ASW) at 22, 15, 10, and 5 degrees C. Depuration of oysters at 22 degrees C had limited effects on reducing V. parahaemolyticus or V. vulnificus in the oysters. Populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 24 publications
3
45
0
1
Order By: Relevance
“…We speculate that the answer may lie in results obtained by our laboratory and many others over the last 30 years. Studies examining the uptake and depuration of V. vulnificus in seeded oysters have all reported that V. vulnificus cells are rapidly taken up but are not retained and are quickly depurated (3,5,6,12,14,31,35). If the oyster microflora is firmly established during the early stages of oyster development, transient bacterial cells acquired through gill filtration could be unable to establish residency in the oyster gut.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the answer may lie in results obtained by our laboratory and many others over the last 30 years. Studies examining the uptake and depuration of V. vulnificus in seeded oysters have all reported that V. vulnificus cells are rapidly taken up but are not retained and are quickly depurated (3,5,6,12,14,31,35). If the oyster microflora is firmly established during the early stages of oyster development, transient bacterial cells acquired through gill filtration could be unable to establish residency in the oyster gut.…”
Section: Discussionmentioning
confidence: 99%
“…However, depuration at low temperature of 15°C has been reported capable of reducing V. parahaemolyticus in the Crassostrea virginica by 2.1 and 2.9 log MPN/g, after 48 hours depuration in UV-treated depuration system [43]. Depuration with refrigerated seawater at 5°C reduced V. parahaemolyticus populations by >3.0 log MPN/g in the Pacific oysters Crassostrea gigas without significant fatality of the oysterswere demonstrated [38].…”
Section: Reduction Of Vibrio In Oystersmentioning
confidence: 99%
“…The tdh gene was detected in four strains, and trh was detected in 23 strains (Figure 2). Several studies have suggested a strong influence of temperature on the concentration of vibrio in marine waters [27][28][29][30] . However, this study only established a correlation with V. vulnifi cus (p < 0.05).…”
Section: Seawater Parametersmentioning
confidence: 99%